A Study of Selective Motor Fitness Components Empowers on Playing Ability In Football: Examining the relationship between selective motor fitness components and playing ability in football players (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Motor  fitness is  a present aptitude  for physical skills,  includes  strength and co-ordination  enriches today’s  Manpower  in players performance.    The study focuses on selected motor fitnesscomponents to ensure the playing ability among low and high performers of Statelevel Football players. To achieve this study, One hundred and fifty  men Football players were randomly selectedas subjects from Haryana State level men Football Tournament held at Karnal in2008-09. Their age ranged from20 to 25 years. Selected subjects were classifiedinto three equal groups of each fifty members. Group 1 served as -Karnal Team,Group-II as Gurgaon and Chandigarh Team and Group III Kaithal and Meerut Team.All the subjects were oriented the purpose of the test and procedure ofconducting this test. Regular activities and training were given that aplombthe player’s  ability  to perform  the game.Questionnaire  preparation  was also done by  our  Research Scholar  with the reference to the review of the literature. The investigator hasprovided onto the following selected motor fitness variables such as Cardio-vascularEndurance, Speed, Agility and Explosive Power. The data is collected with thehelp of five PhD Scholars, Department of Physical Education who were wellversed with the conduct of test and collections under the direct supervision  of  ourResearch  Scholar.  Resulting data will  be collected  before and  after  the competition  and statistically analyzed using ANOVA andDMRT. Hence  the study concluded thatplaying ability solely depends on the physical fitness, stress free mind morethan that it relates the socio-economic status to perform the better strategyof playing games.